A facile one-step synthesis of fluorescent silicon quantum dots and their application for detecting Cu2+. Issue 18 (3rd February 2016) - Liao, Bo; Wang, Wu; Deng, Xiaoting; He, Benqiao; Zeng, Wennan; Tang, Zilong; Liu, Qingquan
Abstract : Fluorescent silicon quantum dots were synthesized by a facile one-step synthesis that involved etching silicon powder through a hydrothermal method. Without any surface modification, these silicon quantum dots could be used as a sensor to detect Cu 2+ . Abstract : Silicon quantum dots (Si QDs) were synthesized by a facile one-step synthesis that involved etching silicon powder through a hydrothermal method. The Si QDs, without any surface modification, maintained good water dispersibility, strong photoluminescence and high pH stability, and can be used as a sensor to detect Cu 2+ .